USING VIDEOANALYSIS AND DIGITAL BIOMECHANICS TECHNOLOGIES IN TEACHING MOTOR ACTIVITIES TO SCHOOLCHILDREN - Mamutov, Polatbay Jumamuratovich (SCIENCE and SOCIETY, 2026)
The article explores the effectiveness of applying video analysis and digital biomechanics technologies in teaching motor skills to schoolchildren. Modern analysis methods, including markerless motion capture and 3D modeling, enable identification of individual movement patterns, correction of technique errors, and reduction of injury risk. Practical recommendations for teachers on integrating these technologies into the educational process are provided.